The Relation Between Cognitive Awareness of Reading Strategies and Writing Anxiety - Gürbüz Ocak; Nilda Hocaoglu (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the cognitive awareness of reading strategies of secondary school students, the relation between the cognitive awareness of reading strategies and writing anxiety, and the common effect of some variables on cognitive awareness of reading strategies. This quantitative study is an example of a relational survey model with correlational research features. Data have been collected through two different scales. 339 secondary school students have participated in this research. Mean, frequencies, standard deviation, Pearson Correlation Coefficient, Simple Linear Regression, and Two Way Anova have been used for data analysis. As a result of the study, secondary school students have good cognitive awareness of reading strategies, and there is a negative relation between cognitive awareness of reading strategies and writing anxiety. Verbal academic success is a predictor of cognitive awareness of reading strategies, and the common effect of gender and writing anxiety doesn’t influence cognitive awareness of reading strategies.